Ankle Joint Function in the Lower Limb Impact Absorption Mechanism of Normal Gait - HIIRAGI, Yukinobu; FURUYA, Tomoiki (Rigaku ryoho kagaku, 2017)
[Purpose] We aimed to clarify the main part where shock absorption is carried out by using an acceleration sensor. [Subjects and Methods] The subjects were eleven healthy male subjects, average age, 20.8 ± 2.44 years old. Acceleration was measured with sensors attached to the calcaneus, fibula and lateral part of the thigh, and the statistical significance of differences was examined using the Friedman test (Tukey’s method). [Results] Acceleration (deg/sec/BW/WS) at the calcaneus, femoral head and thigh were 4.2 ± 1.2, 0.2 ± 0.03, 0.1 ± 0.06, respectively. RMS (m/s2 rms/WS2) of the same sites were 68.7 ± 20.9, 5.4 ± 0.8, and 3.7 ± 1.6, respectively. There were significant differences (p<0.01) between the accelerations at the calcaneus and the fibula portion, and between the accelerations at the calcaneus and the femoral region. There was no significant difference between the accelerations at the fibula and the thigh. There were significant differences between the RMS values at the calcaneus and the fibular head (p<0.05), and between the RMS values at the calcaneus and the thigh (p<0.01). There was no significant difference between the RMS values at the fibula head and the thigh. [Conclusion] The results show that the impact during normal gait is mainly absorbed by the ankle joint.